132k views
1 vote
Factorise the expression (c+2d)^2-(c+2d)(3c-7d)

2 Answers

7 votes

Answer:

(c + 2d) • (9d - 2c)

Step-by-step:

Step 1 :

Equation at the end of step 1 :

((c + 2d)2) - (c + 2d) • (3c - 7d)

Step 2 :

Pulling out like terms :

2.1 Pull out c+2d

After pulling out, we are left with :

(c+2d) • ( (c+2d) +( (-1) * (3c-7d) ))

User Ramanujan R
by
6.5k points
2 votes

Answer:

(c+2d)(9d - 2c) =
5dc - 2c^(2) + 18d^(2)

Explanation:


(c+2d)^(2) - (c+2d)(3c-7d)


(c+2d)(c+2d) - (c+2d)(3c-7d)

Both sides have (c+2d) so pull out (c+2d)

  • Rule: a.b + a.c = a(b+c)
  • Rule: a.b - a.c = a(b-c)

(c+2d) [(c+2d) - (3c-7d)]

(c+2d) [c+2d - 3c +7d]

(c+2d) [-2c + 9d] = (c+2d)(9d - 2c)

  • Rule: (a+b)( c + d) = ac + ad + bc + bd ==> Foil method

(c+2d)(9d - 2c) =
9dc - 2c^(2) + 18d^(2) -4dc =
5dc - 2c^(2) + 18d^(2)

Hope this helps ^-^

User Robert Ros
by
6.2k points